2016
DOI: 10.1016/j.jval.2016.09.1217
|View full text |Cite
|
Sign up to set email alerts
|

Exploring The Impact of Adding A Respiratory Dimension to The EQ-5D-5L

Abstract: Objectives. To evaluate the impact of adding a respiratory dimension (a bolt-on dimension) to the EQ-5D-5L health state valuations. Methods. Based on extensive regression and principal component analyses, 2 respiratory bolt-on candidates were formulated: R1, limitations in physical activities due to shortness of breath, and R2, breathing problems. Valuation interviews for the selected bolt-ons were performed with a representative sample from the Dutch general public using the standardized interview protocol an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“… 34 Hoogendoorn et al proposed another potential solution for future consideration, which involved the addition of a respiratory dimension to the EQ-5D (3L or 5L). 44 They found that addition of a “breathing problem” dimension significantly improved the responsiveness of the EQ-5D to clinically significant changes in chronic lung disease patients. 44 However, such an approach would require valuation of the new dimension in order to obtain preference-based utility scores, which can be burdensome in terms of time and resources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 34 Hoogendoorn et al proposed another potential solution for future consideration, which involved the addition of a respiratory dimension to the EQ-5D (3L or 5L). 44 They found that addition of a “breathing problem” dimension significantly improved the responsiveness of the EQ-5D to clinically significant changes in chronic lung disease patients. 44 However, such an approach would require valuation of the new dimension in order to obtain preference-based utility scores, which can be burdensome in terms of time and resources.…”
Section: Discussionmentioning
confidence: 99%
“… 44 They found that addition of a “breathing problem” dimension significantly improved the responsiveness of the EQ-5D to clinically significant changes in chronic lung disease patients. 44 However, such an approach would require valuation of the new dimension in order to obtain preference-based utility scores, which can be burdensome in terms of time and resources. Additionally, the comparability of the utilities obtained using this instrument with established national tariffs may also be questionable.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 28 articles that were included, 3 articles were studies that identified possible bolt-ons (category A "identification or development of possible suitable bolt-ons"), [23][24][25] 13 articles were psychometric performance studies (category B "psychometric performance studies"), 8,26-37 and 6 articles were valuation studies of EQ-5D 1 bolt-on (category C "health state valuation studies"). 19,20,[38][39][40][41][42] Furthermore, 3 articles were categorized as both categories A and B, [43][44][45] and 3 articles as both categories A and C. 13,21,38 Study populations consisted of a healthy population (n = 17 articles: general public, 13,[19][20][21]24,25,27,30,36,38,[40][41][42][43] random households, 44,45 faculty members 39 ) and patients (n = 11 articles: individuals with a chronic condition, 23 visitors of an outpatient eye clinic, 26 cognitive impaired elderly patients, 18 patients with diabetes, 28 general injury patients, 29,31,35 patients listed for cataract surgery, 32,34 stroke patients, …”
Section: Study Characteristicsmentioning
confidence: 99%
“…Overall, only 1 study scored "doubtful" on the COSMIN Risk of Bias checklist, whereas all other studies scored "inadequate." Considering the quality of studies per subject, 1 study scored "adequate" on PROM development, 38 3 studies scored doubtful, 21,28,42 and 24 studies scored inadequate. Furthermore, content validity was found to be inadequate again in 25 studies and doubtful in the remaining 3 studies.…”
Section: Quality Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation